Teaching tribals through gramsevak & voluntary agency - Waghmare, Sevakram K., 1943-; Patel, M. R.; Patel, R. M. (New Delhi : Metropolitan Book, 1988)
Study relates to Valsad and The Dangs, districts of Gujarat
Bibliography: p. 204-207
Keywords: Agricultural extension work -- India -- Gujarat; Rural development -- India -- Gujarat; Gujarat (India) -- Scheduled tribes